Epidemiology of General Obesity and Abdominal Obesity among People in Hilly Areas of North India: A Hospital Based Study - Arti Gupta; Venkatashiva Reddy B; Vandhana Semwal; Amit Kumar Singh (Medsci Publications, 2017)
Background & objectives: In today's world, obesity is a lifestyle disease that can kill. This study was conducted to assess the prevalence of general and abdominal obesity among adult outdoor patient in Urban and Rural Health Training Centre, Department of Community Medicine, Veer Chandra Singh Garhwali Government Medical Sciences and Research Institute, Srinagar, Uttarakhand. Methods: A total of 200 patients aged ≥20 years were randomly selected were studied. Simplified questionnaire was used for interviewing participant and anthropometric measurement was done. Definition of overweight and obesity given by the World Health Organization (WHO); Asia Pacific Guidelines; and WHO criteria for Europids were used. Results: Participants aged from 20-74 years and 56.5% were females. Prevalence of abdominal obesity was found 38.5% (24.1% for men and 49.6% for women, p<0.05) using WHO Asia Pacific Guidelines. By WHO obesity criteria for europids, the prevalence of abdominal obesity was 19.5% (11.5% for men and 25.7% for women, p<0.05).Multiple logistic regression analysis showed women and not working patients had a higher risk of general obesity and abdominal obesity than working men with p <0.05. Conclusions: The prevalence of abdominal, as well as of general obesity, was high using WHO Asia Pacific Guidelines. Gender and occupation were risk factors associated with obesity. Suitable healthcare strategies are needed for combating obesity.